Centros de rehabilitación social de Ecuador como mecanismo de segregación - Márquez Gómez, Nathaly Michelle (Machala, Utmachala, 2023)
Currently, the social rehabilitation centers (CRS) in Ecuador have become one of the most serious problems in the country, especially due to the continuous prison massacres and the collapse of the organizational infrastructure of the social rehabilitation system regulated by the National Comprehensive Care Service. to Adult Persons Deprived of Liberty and Adolescent Offenders (SNAI), for this reason it is imperative to seek solutions to these dramatic realities presented in the Social Rehabilitation Centers of the country. Due to this background, the objective of carrying out an exploratory analysis was proposed to identify the main problems of the SRCs in Ecuador, which allows for an overview of the panorama and, based on this, to present brief recommendations to mitigate the organizational problem. In the study, a basic predictive research methodology will be used, in terms of the socio-critical research paradigm and, in turn, the use of theoretical methods (Analysis - synthesis, exegetical and sociological) and empirical (documentary analysis) especially of scientific articles. of the last 5 years. It was identified that the current prison system uses the prison as a mechanism of segregation for the most disadvantaged economic classes. In fact, due to the serious economic crisis that Ecuador is experiencing and the severity of the prison system, we have that the social classes with the greatest economic limitations become the main "clients" of the prisons. Thus, vulnerable social groups excluded from society, generally located in the most remote neighbourhoods, or those whose economic income does not allow them to satisfy their basic needs, become the main targets and recipients of criminal law and, once absorbed by the prison system, these conditions are aggravated and worsened in prisons
En la actualidad los centros de rehabilitación social (CRS) en Ecuador se han convertido en una de la problemática más grave del país, especialmente por las continuas matanzas carcelarias y colapsos de infraestructura organizacional del sistema de rehabilitación social regulado por el Servicio Nacional de Atención Integral a Personas Adultas Privadas de la Libertad y Adolescentes Infractores (SNAI), por ello es imperioso buscar soluciones a estas realidades dramáticas presentadas en los Centros de Rehabilitación Social del país. Debido a este antecedente se planteó el objetivo de realizar un análisis exploratorio para identificar las principales problemáticas de los CRS del Ecuador, que permita tener una visión general del panorama y a partir de ello presentar breves recomendaciones para mitigar el problema organizacional. En el estudio se utilizará una metodología de investigación de tipo básica predictiva, en cuanto al paradigma de la investigación socio crítico y a su vez la utilización de métodos teóricos (Análisis - síntesis, exegético y sociológico) y empíricos (Análisis documental) especialmente de artículos científicos de los últimos 5 años. Se identificó que el sistema penitenciario actual utiliza la cárcel como mecanismo de segregación para las clases económicas más desfavorecidas. De hecho, debido a la grave crisis económica que vive Ecuador y a la severidad del sistema penitenciario, tenemos que las clases sociales con mayores limitaciones económicas se conviertan en las principales "clientes" de las cárceles. Así, los grupos sociales vulnerables excluidos de la sociedad, ubicados por lo general en los barrios más alejados, o aquellos cuyos ingresos económicos no les permiten satisfacer sus necesidades básicas, se convierten en objetivos y principales destinatarios de la norma penal y, una vez absorbidos por el sistema penitenciario, estas condiciones se agravan y empeoran en las cárceles.
Keywords: Centros de rehabilitación social; Ecuador; mecanismo de segregación